Trade Dispute between the EU and Indonesia over Indonesian Steel Product - Putri, Cici Amilia (JLAST : Journal of Law and Social Transformation, 2023)
This paper examines the trade dispute between the European Union (EU) and Indonesia over Indonesian steel goods. The EU's application of customs duties and anti-dumping measures on Indonesian steel products spurred Indonesia to initiate a dispute with the World Trade Organisation (WTO), claiming breaches of the bilateral agreement struck by the two countries. The WTO's creation of a trade dispute tribunal needs compliance from both Indonesia and the EU. This study uses qualitative approaches to critically assess relevant material, including scholarly journals, papers, and news sources, to provide light on the motives behind the EU's adoption of customs and anti-dumping policies, showing underlying domestic interests. Despite the EU's displeasure with Indonesia's remedy, it is still within Indonesia's sovereign rights to take such moves. This case highlights the complexities of international trade agreements, as well as the need to follow WTO norms for settling disputes.